An Unconditionally Stable Difference Approximation for a Class of Nonlinear Dispersive Equations (Journal of Computational Mathematics, 1991)
An unconditionally stable leapfrog finite difference scheme for a class of nonlinear dispersive equations is presented and analyzed. The solvability of the difference equation which is a tridiagonal circular linear system is discussed. Moreover, the convergence and stability of the difference scheme are also investigated by a standard argument so that more difficult priori estimations are avoided. Finally, numerical examples are given.